2012
DOI: 10.1111/jnc.12041
|View full text |Cite
|
Sign up to set email alerts
|

1α,25‐Dihydroxyvitamin D3‐liganded vitamin D receptor increases expression and transport activity of P‐glycoprotein in isolated rat brain capillaries and human and rat brain microvessel endothelial cells

Abstract: MDR1/P-gp induction by the vitamin D receptor (VDR) was investigated in isolated rat brain capillaries and rat (RBE4) and human (hCMEC/D3) brain microvessel endothelial cell lines. Incubation of isolated rat brain capillaries with 10 nM of the VDR ligand, 1α,25-dihydroxyvitamin D3 [1,25(OH)2D3] for 4 h increased P-gp protein expression (4-fold). Incubation with 1,25(OH)2D3 for 4 or 24 h increased P-gp transport activity (specific luminal accumulation of NBD-CSA, the fluorescent P-gp substrate) by 25 – 30%. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 55 publications
8
41
0
Order By: Relevance
“…It appears that activation of P-gp protein is preceded by an increase in P-gp mRNA which is also associated with activation of the nuclear factor kappa B (NF-kB) (Zhang et al 2014; Fan et al 2015). In isolated rat and human brain microvessel endothelium, vitamin D3-liganded vitamin D receptor increases P-gp mRNA expression and increases P-gp transporter expression (Durk et al 2012). It has been shown that fetal expression of P-gp is very high and falls progressively with age in the post-natal period.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that activation of P-gp protein is preceded by an increase in P-gp mRNA which is also associated with activation of the nuclear factor kappa B (NF-kB) (Zhang et al 2014; Fan et al 2015). In isolated rat and human brain microvessel endothelium, vitamin D3-liganded vitamin D receptor increases P-gp mRNA expression and increases P-gp transporter expression (Durk et al 2012). It has been shown that fetal expression of P-gp is very high and falls progressively with age in the post-natal period.…”
Section: Discussionmentioning
confidence: 99%
“…VDRresponsive transporters include the rat apical sodium-dependent bile acid transporter (Asbt) (10), human organic aniontransporting polypeptide (OATP1A2) (21), multidrug resistance protein-1 or P-glycoprotein (MDR1/P-gp) (44), and the human and rodent multidrug resistance-associated proteins (MRP2/Mrp2, Mrp3, MRP4/Mrp4) both in vitro and in vivo (14,22). Our laboratory has shown that VDR transactivates P-gp in brain microvessel endothelia (18) in vitro and P-gp in murine kidney and brain but not ileum and liver in vivo, leading to hastened efflux of digoxin in the brain and kidney (11).…”
mentioning
confidence: 99%
“…, insulin, transferrin, leptin); bi) absorptive mediated transcytosis ( e.g. , albumin) and active transport systems for glucose and other essential nutrients (aminoacids); c) transport activity of P-gp in response to Vitamin D (93); d) modulatory mechanisms of blood-brain barrier P-gp transport activity (94); and e) transendothelial transport of fluorescent drugs by confocal microscopy (95). In addition, these brain microvessels once purified are a viable source of brain microvascular endothelial cells which can be isolated from these microvessel fragments allowing the preparation of a relatively pure BBB endothelial primary culture (96).…”
Section: Isolated Brain Microvesselsmentioning
confidence: 99%